IoT-Based Air Conditioner Monitoring and Control at PT XYZ: A Prototype Approach Utilizing Node MCU ESP8266, Relay Modules, and DHT11 Temperature Sensors - Innaya, Thalia Gemi; Junaidi, Akmal; Alfikri, Fadli; Kurniawan, Didik; Iqbal, Muhammad (Magister Program of Mathematics, Universitas Lampung, 2025)
This study presents the development and implementation of an IoT-based monitoring and control system for air conditioners (AC) at PT XYZ. Leveraging the capabilities of Node MCU ESP8266, relay modules, and DHT11 temperature sensors, the proposed system enables real-time monitoring of AC status and room temperature. It also facilitates control over individual and multiple AC units, thereby enhancing operational efficiency. The system’s design focuses on energy efficiency, aiming to reduce unnecessary power consumption by ensuring that AC units are active only when needed. The system includes features for monitoring the AC’s on/off status and providing historical temperature data through graphical charts. This real-time data display allows users to track temperature trends and make informed decisions regarding AC operation. The prototype approach employed in this research involves several stages: communication with stakeholders, planning, modeling, prototype development, deployment, and iterative feedback. Testing results indicate that the system effectively meets the research objectives by providing accurate temperature readings and reliable AC control. Compared to existing solutions, this system offers enhanced functionality and integration, contributing to energy savings and improved management of AC units. This research contributes to the field by addressing gaps identified in previous studies and demonstrating the practical application of IoT technology in energy management for air conditioning systems.